Why Scorsese is Right About Corporate Power - James McMahon (Class, Race and Corporate Power, 2022)
In the March 2021 issue of Harper's, Scorsese wrote an essay to pay tribute to Federico Fellini, the Italian director who directed such great films as La Strada, 8 1/2, La Dolce Vita, Nights of Cabiria and Satyricon. Scorsese writing on Fellini is definitely newsworthy for cinephiles who want to know about Fellini's beginnings in Italian neo-realism (for example, he worked with Rosselini on Rome, Open City), or who simply want to be reminded of why his filmography is so great. However, the news of this essay's arrival went well beyond film studies and had very little to do with Fellini. People were talking about the essay because Scorcese framed his tribute to Fellini – which was both personal and knowledgeable – with an argument about the decline of cinema as an art form. This paper explains why Scorsese is right about the differences that exist between himself and a director like Fellini. In fact, we can use Scorsese's argument as a platform to widen our perspective on the political economy of Hollywood. The story Scorsese is telling about the business of Hollywood is a story about business interests wanting to reduce risk. The ambiguity of risk in this story – is it financial risk or is it aesthetic risk? – is a helpful shortcut to understanding what reducing risk means for those who have control over the industrial art of filmmaking. When the Hollywood film business is estimating its future earnings, risk perceptions account for the possibility that the future of culture will be different–and perhaps radically different–from what capitalists expect it to be. This logic of capitalist accounting, while quantitative in expression (prices, income, volatility, etc.), is social in essence. For this reason, the capitalization of cinema cannot overlook any social dimension of cinema, be it aesthetic, political or cultural. The eye of capitalization searches for any social condition that could have an impact on "the level and pattern of capitalist earnings" (Nitzan & Bichler, 2009, p. 166). This paper is a lightly edited compilation of a two-part series originally published by Notes on Cinema in June and July, 2021. It has been re-published here with permission of the author.
Keywords: P16; 330; art; capital; cinema; corporation; Hollywood; power; risk